The Role of Digital Economy to Enhancing Sustainable Economic Development - Nur Aini Fitriya Ardiani Aniqoh (Universitas Pendidikan Ganesha, 2020)
This study analyzes The Role of Digital Economy to Enhancing Sustainable Economic Development. The general objective of this research is to assist the government in determining the right policy on the implement of digital economy and its impact on the the sustainable economic development, especially in Indonesia. In Indonesia the digital economy has increasingly developed in the field of ecommerce. The ecommerce industry is not merely talking about buying and selling goods and services via the internet. But there are also other things in it such as inter-service providers, telecommunications providers and others. This is the reason why the ecommerce industry must be adapted to be able to push the economic pace forward. The government is currently declaring Indonesia as the largest digital economy in 2020 and is targeted to be the largest in Southeast Asia. One of the foundations of national development in this declaration is the digital sector. The government targets ecommerce transactions to reach US 130 billion and creates 1,000 technopreneur with a business value of US 10 billion in 2020. Therefore this research will provide policy benefits in strengthening government institutions in order to control the implementation of digital economy in Indonesia so that it give the positive impact on the sustainable economic development to be able to prosper the community and have a positive impact on the environment and increasing the economic value.